(untitled) (KYAMC Journal, 2024)
For the afflicted female, Diminished Ovarian Reserve (DOR) has disastrous effects on her quality of life, fertility, fecundity, and general well-being. Gynecological operations and chemotherapy can also make DOR worse. By evaluating the gonadotoxicity and effectiveness of current chemotherapy regimens as well as the techniques used in gynecological procedures, the best regimen or technique can be chosen after a risk-benefit ratio study. This ought to be carried out in concert with methods for preserving fertility, such as cryopreservation, ovarian transposition and suppression, and medication. To meet the demand for oncofertility, novel strategies utilizing fertoprotective agents must be assessed. This guarantees the greatest protection of the follicular pool and the least amount of harm to the ovarian environment and function. KYAMC Journal Volume: 15, No: 01, April 2024: 50-55.